HUBUNGAN MOTIVASI DAN PEMANFAATAN SARANA BELAJAR DENGAN HASIL BELAJAR SENI BUDAYA DALAM BIDANG SENI RUPA KELAS VII DI SMP N 16 PADANG - Rio Indra Wadi, Dr. Yahya, M.Pd., Drs. Efrizal, M.Pd. (Serupa The Journal of Art Education, 2016)
and utilize of facilities with learning outcome at SMP N 16 Padang. Type of data analysis in this research is product moment correlation which is done by using SPSS 16.0 version. Based on the data, the result of motivation of study and learning outcome, coefficient correlation’s level was 0.250*. The significant score was 0.010 < 0.05 and correlation between motivation to learn and learning outcome, coefficient correlation’s level was 0.925” the significant score was 0.000 < 0.05. Motivation to learn gives contribution amount 6.25% with learning outcome. It can conclude that there is a significant correlation between motivation to learn and utilize of facility with learning outcome in SMP N 16 Padang at VII grades.Kata Kunci: motivasi belajar, pemanfaatan sarana belajar, hasil belajar seni rupa